EQUITABLE DISTRIBUTION OF EDUCATION THROUGH THE BANUH, BASA, TABA PROGRAM, BY ISLAMIC BOARDING SCHOOLS AL-ISLAH BONDOWOSO - Arrozi, Fatahillah (Tsaqofah : Jurnal Pendidikan Islam, 2022)
The purpose of this research is to find out how the concept of equal education is applied through the Banuh, Basa, Taba program by Pondok Pesantren Al-Ishlah Bondowoso. We use a qualitative research approach with a case study design as a method in this research, the research site is the Al-Ishlah Dadapan Bondowoso Islamic Boarding School, the kyai and asatidz and students we determine as the subject of this research, the data collected in the form of words and writings and images, the researcher acts as an instrument, to collect data we conduct in-depth interviews accompanied by observation, after the raw data is collected, it will be reduced, presented, and then drawn conclusions. From the results of this study, it can be concluded that for equal distribution of education to all economic statuses of society, an independent program is needed from each educational institution. Such as the concept of cross-marrying education costs through the Banuh, Basa, and Taba programs. In addition, additional business units are also needed to support existing education financing. As applied by Al-Ishlah Islamic Boarding School with its protection economy concept. Keywords: equalization of education, boarding school